1984
DOI: 10.1161/01.hyp.6.5.605
|View full text |Cite
|
Sign up to set email alerts
|

Influence of androgen on translatable renin mRNA in the mouse submandibular gland.

Abstract: SUMMARY In mature outbred Swiss male mice, submandibular gland renin enzyme activity is 4-and 10-fold higher than in glands of prepubescent males and mature females, respectively. Levels of translatable renin mRNA have been studied in mouse submandibular gland during postnatal development and following administration of testosterone. The [ 35 S]methionine-labeled cell-free translation products directed by male glandular mRNA contain a 47 ± 2 kd renin precursor that is not detected in products coded by prepubes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0
1

Year Published

1987
1987
2000
2000

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 27 publications
2
7
0
1
Order By: Relevance
“…ANOVA, p < 0.00 1. (20), though levels o f neither growth hormone nor prolactin peak or change at the times when renin production by SMG changes (20 (3,17). The results o f the present study support this concept.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…ANOVA, p < 0.00 1. (20), though levels o f neither growth hormone nor prolactin peak or change at the times when renin production by SMG changes (20 (3,17). The results o f the present study support this concept.…”
Section: Discussionsupporting
confidence: 66%
“…Renin enzyme levels in SMG increase greatly with onset of puberty in an androgen-dependent manner (3,4,6). The present study suggests that there are also changes in the biosynthetic processing of active renin in the SMG during ontogeny, with a relative increase in 2-chain renin in the mature male animal.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In studies using the mouse submaxillary or submandibular gland, which contains an enzyme physiologically, chemically, and immunologically similar to renal renin, it was reported that the intervention of androgens was needed to elevate renin above the basal level [62]. These findings also demonstrated that androgens increase the renin activity by inducing an increase in the level of translatable renin precursor mRNA [49]. Moreover, it was recently reported that, in male CD-1 mice, renin expression in some extrarenal tissues, including the testis, may be stimulated by androgens [26].…”
Section: Discussionmentioning
confidence: 96%
“…The regulation of tissue renin and angiotensinogen gene expression for controlling tissue production of these polype- Effects of long-term fibrosis in rats administration of captopril on spontaneous myocardial ptide were studied by a number of investigators in submandibular gland demonstrating that cytoplasmic renin mRNA was accumulated in response to testosterone (Wilson et al 1981;Pratt et al 1981Pratt et al , 1984. Little is known about the regulation of myocardial renin-angiotensin system, but androgen may accumulate cytoplasmic renin mRNA which potentially influence myocardial function.…”
Section: Discussionmentioning
confidence: 99%